Codes, cryptology and information security : second International Conference, C2SI 2017, Rabat, Morocco, April 10-12, 2017, Proceedings -- In honor of Claude Carlet /: second International Conference, C2SI 2017, Rabat, Morocco, April 10-12, 2017, Proceedings -- In honor of Claude Carlet. (2017) - Unknown
No abstract available